2021
DOI: 10.1016/j.bioactmat.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Flexible electrical stimulation device with Chitosan-Vaseline® dressing accelerates wound healing in diabetes

Abstract: The healing process of diabetic wounds is typically disordered and prolonged and requires both angiogenesis and epithelialization. Disruptions of the endogenous electric fields (EFs) may lead to disordered cell migration. Electrical stimulation (ES) that mimics endogenous EFs is a promising method in treating diabetic wounds; however, a microenvironment that facilitates cell migration and a convenient means that can be used to apply ES are also required. Chitosan-Vaseline® gauze (CVG) has been identified to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 88 publications
1
47
0
Order By: Relevance
“…Results showed that high voltage monophasic pulsed current increased vascular endothelial growth factor levels, promoted cell migration and proliferation and decreased scar tissue formation. 95 …”
Section: Treatment Options That Promote Wound Healing When Used In Combination With Hydrogels and Creamsmentioning
confidence: 99%
“…Results showed that high voltage monophasic pulsed current increased vascular endothelial growth factor levels, promoted cell migration and proliferation and decreased scar tissue formation. 95 …”
Section: Treatment Options That Promote Wound Healing When Used In Combination With Hydrogels and Creamsmentioning
confidence: 99%
“…The beneficial effect of ES was also seen in other diabetic-related wounds whereby a chronic wound at a post-amputation stump site of nearly 1-year duration closed completely after 45 sessions of ES [102]. In pressure ulcers, amazing recovery was seen in HVMPC [84][85][86]103]. The outcome of ES was comparable to the negative pressure wound therapy (NPWT) in a study of pressure ulcers [104].…”
Section: Types Of Cellmentioning
confidence: 86%
“…PC is widely studied as it has lesser electrothermal, electrophysical, and electrochemical side effects compared to DC due to the pulsing features of PC [48]. Most PC protocols deliver less than 20 mA, and high voltage monophasic pulsed current (HVMPC), as shown in Figure 4c, is the most common PC with twin spikes of high voltage (100-500 V) current delivered in a pair within 2-50 ms [84][85][86][87]. The field strength, exposure duration, and duty cycle affect the galvanotaxis of cells but not the frequency [48].…”
Section: Pulsed Current (Pc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current treatment, the wound healing of diabetes can not be improved [30][31][32]. After the trauma, it will lead to a series of diseases, leading to chronic in ammation and the production of a large number of reactive oxygen species [33,34].…”
Section: Discussionmentioning
confidence: 99%